PANDANGAN DUNIA DALAM NASKAH DRAMA HĀRŪT WA MĀRŪT KARYA ALĪ ACHMAD BĀKATSĪR - Rahmat Hidayat (Arabic Literature Department, 2014)
This research discusses the following: (1) How is the text structure of Hārūt Wa Mārūt play script by Alī Achmad Bākatsīr? (2) How is the authors‟ world view which is reflected in Hārūt Wa Mārūt play script? The objectives of this research are: (1) To describe the text structure of Hārūt Wa Mārūt play script by Alī Achmad Bākatsīr (2) To describe the author‟s world view Hārūt Wa Mārūt play script by Alī Achmad Bākatsīr. According to the result of this research, the following conclusion can be drawn: first, from the text structure there are three visions as follows: the vision of God which is represented by the characters with the divinity characteristics such as virtue and fidelity; the vision of world which is represented by the characters with worldliness or secular characteristics with badness tendency; and the vision of human which is represented by the characters with human characteristics who is setting out their desire. Second, the author wants to deliver his ideology which has Islamic reformer by putting the precept of God into his works and combining it in history or politic which is related to the reality. World view obtained after theresearch is social realism.